An Adaptive System for Home Monitoring Using a Multiagent Classification of Patterns. (17th April 2008) - Rammal, Ali; Trouilhet, Sylvie; Singer, Nicolas; Pécatte, Jean-Marie
Abstract : This research takes place in theS ( MA ) 2 D project which proposes software architecture to monitor elderly people in their own homes. We want to build patterns dynamically from data about activity, movements, and physiological information of the monitored people. To achieve that, we propose a multiagent method of classification: every agent has a simple know-how of classification. Data generated at this local level are communicated and adjusted between agents to obtain a set of patterns. The patterns are used at a personal level, for example to raise an alert, but also to evaluate global risks (epidemic, heat wave). These data are dynamic; the system has to maintain the built patterns and has to create new patterns. So, the system is adaptive and can be spread on a large scale.